Relevansi Kurikulum Pendidikan Islam di Madrasah dengan Kebutuhan Dunia Modern - Muhtar Hidayat; Sukari Sukari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the adaptation of Islamic education curriculum in madrasahs in facing the challenges of modern development. The main focus is on the limitations that hinder the implementation of relevant curriculum, including resource limitations and integration between religious knowledge and science. This study is categorized as qualitative, namely research that produces descriptive data in the form of written words. Literature research or also called library research is a type of research that limits activities only to library collection materials and document studies without requiring field data (field research). Through a qualitative approach, this study suggests the need for curriculum updates involving digital technology, improving teacher competency, and collaborating with industry. This study also highlights the importance of developing digital literacy skills and critical thinking to prepare students for the global workforce. This study found that the main challenges in adapting Islamic education curriculum in madrasahs do not guarantee the absence of human resources, limited facilities, and resistance to change. The importance of technology integration, strengthening teacher competency, and collaboration between madrasahs, families, and communities are also revealed as factors that can increase the effectiveness of the curriculum. In addition, a curriculum is needed that supports 21st century skills to face the development of the times.